2017
DOI: 10.1016/j.earlhumdev.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Smell and taste in the preterm infant

Abstract: Olfaction and gustation are critical for the enjoyment of food but also have important metabolic roles, initiating the cephalic phase response that sets in train secretion of hormones important for metabolism and digestion before any food is actually ingested. Smell and taste receptors are functional in the fetus and there is evidence for antenatal learning of odours. Despite enteral nutrition and metabolism being major issues in the care of very preterm infants, often little consideration is given to the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The routine use of providing a smell and taste of maternal milk to babies prior to enteral feeds to provide the cues of maternal odour seems to be an emerging practice in some units; however, there is minimal evidence of its benefits . Smell and taste initiate a metabolic response through the secretions of hormones insulin and ghrelin; taste receptors are apparent from 18 weeks’ gestation and flavour perception from 24 weeks’ gestation .…”
Section: Discussionmentioning
confidence: 99%
“…The routine use of providing a smell and taste of maternal milk to babies prior to enteral feeds to provide the cues of maternal odour seems to be an emerging practice in some units; however, there is minimal evidence of its benefits . Smell and taste initiate a metabolic response through the secretions of hormones insulin and ghrelin; taste receptors are apparent from 18 weeks’ gestation and flavour perception from 24 weeks’ gestation .…”
Section: Discussionmentioning
confidence: 99%
“…Fetal and neonatal sensory discrimination capabilities have been described in different altricial species (rabbits, sheep, rats) including humans (Lecanuet et al, 1995;Schaal et al, 2002Schaal et al, , 2004Clark-Gambelunghe and Clark, 2015;Fulgione et al, 2017). Neuroethological studies indicate that chemosensory systems rapidly become functional in the uterus (Molina et al, 1999(Molina et al, , 2007aSchaal et al, 2004;Bloomfield et al, 2017). This development is required for essential survival purposes related to subsequent maternal attachment processes including the discrimination and recognition of the main nutrients (colostrum and milk) that will be provided both peri-and neonatally (Cernoch and Porter, 1985;Makin and Porter, 1989;Marlier et al, 1998;Miller and Spear, 2009;Díaz-Marte et al, 2010;Corona and Lévy, 2015).…”
Section: Do Fetuses Perceive Etoh's Chemosensory Properties?mentioning
confidence: 99%
“…A second experimental approach validating the importance of prenatal exposure to EtOH's sensory properties has been employed during a fetal stage of brain development in the rat analogous to the 2nd human trimester (Dobbing and Sands, 1979;Tran et al, 2000). During this stage rats and humans exhibit a functional olfactogustatory system (Molina et al, 1999;Bloomfield et al, 2017) as well as significant innervations of target fields of the oral trigeminal system (Mbiene and Mistretta, 1997). The procedure normally involves maternal EtOH intoxication utilizing subteratogenic doses (0.5-2.0 g/kg) that are intragastrically administered during the last 4 days of gestation (gestational days 17-20).…”
Section: Do Fetuses Perceive Etoh's Chemosensory Properties?mentioning
confidence: 99%
“…Olfaction is sufficiently mature in the fetus between 26 and 28 weeks (Bloomfield et al, 2017). In previous research, preterm infants with 28 weeks of gestation showed distinguished reactions in response to different scents (Goubet et al, 2002).…”
Section: Introductionmentioning
confidence: 87%